Comparison of steady and unsteady RANS CFD simulation of a supersonic ORC turbine. (September 2017) - Obert, Benoit; Cinnella, Paola
Abstract: This article presents computational fluid dynamics (CFD) simulations of a supersonic flow inside the first stage of an Organic Rankine Cycle (ORC) turbine. The expander considered in this work is the first stage of a three-stage axial turbine that uses hexamethyldisiloxane (MM) as the working fluid. The thermodynamic properties of the working fluid are modelled by a Helmoltz free energy-based equation of state during both the design and simulation steps to accurately account for the non-ideal nature of the fluid under the considered conditions. The high expansion ratio of the turbine leads to a supersonic flow in the stator and rotor blade passages. The design of the stator blade shape is carried out by means of the generalized method of characteristics (MOC). The CFD code used in this work is the commercial ANSYS CFX solver and the simulations are based on the two-dimensional Reynolds-Averaged Navier-Stokes (RANS) equations supplemented by a k-ω turbulence model. Results provided by steady mixing plane simulations are compared to those of unsteady sliding mesh simulations in order to understand the implications of stator/rotor flow interaction on blade loading, torque, entropy generation and flow structure.